2019
DOI: 10.2147/ndt.s194924
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association study of the excitatory amino acid transporter 2 (EAAT2) and glycine transporter 1 (GlyT1) gene polymorphism with schizophrenia in a Polish population</p>

Abstract: Background: Excitatory amino acid transporter 2 encoded by SLC1A2 is responsible for approximately 90% of glutamate uptake. Glycine transporter 1, encoded by SLC6A9 , is responsible for maintaining a low concentration of the N-methyl-D-aspartate receptor (NMDAR) co-agonist – glycine in the synaptic cleft, suggesting its participation in the development of the NMDARs hypofunction described in schizophrenia. Aim: The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…These authors detected three silent mutations in the coding region, C894T in exon 5, C1134T in exon 7, and C1476T in exon 9 (202), highlighting that a role of these variants in the pathogenesis of SCZ is unlikely. Similarly, subsequent case-controls studies confirmed these negative findings (203)(204)(205)(206). Another negative finding derived from a gene expression analysis in post-mortem dorsolateral prefrontal cortex and cerebellum brain samples (207).…”
Section: Genetics Of Glycinergic Pathway In Schizophreniamentioning
confidence: 65%
See 1 more Smart Citation
“…These authors detected three silent mutations in the coding region, C894T in exon 5, C1134T in exon 7, and C1476T in exon 9 (202), highlighting that a role of these variants in the pathogenesis of SCZ is unlikely. Similarly, subsequent case-controls studies confirmed these negative findings (203)(204)(205)(206). Another negative finding derived from a gene expression analysis in post-mortem dorsolateral prefrontal cortex and cerebellum brain samples (207).…”
Section: Genetics Of Glycinergic Pathway In Schizophreniamentioning
confidence: 65%
“…The authors performed two proofof-principle clinical trials with glycine and d-cycloserine obtaining an additional 20 to 26% reduction in symptom severity with the former and 13 to 30% reduction with the latter (201) Conversely, a series of negative studies do not appear to support a role for glycine transmission and signaling in SCZ molecular pathophysiology, at least on genetics ground. (202)(203)(204)(205)(206). The study of Feng et al (202) explored the role of genetic mutations within the glycine receptor a2 subunit gene (GLRA2) in SCZ, using a sequencing approach.…”
Section: Genetics Of Glycinergic Pathway In Schizophreniamentioning
confidence: 99%
“…As far as we know, only a few studies on genetic polymorphism of SLC1A2 in MDD were conducted. The majority of studies reported an association of SLC1A2 SNPs with bipolar disorder [46,47,48,49] and schizophrenia [50,51,44]. One of the polymorphisms (-181 A/C, rs4354668) evaluated in this paper was also analyzed in a Thai sample of 100 patients with MDD with and without suicide attempt [52].…”
Section: Discussionmentioning
confidence: 99%
“…Purity and concentration of DNA extracts was assessed using a BioPhotometer plus (Eppendorf AG, Germany). The genotyping of SNPs: rs4354668 A/C in the SLC1A2 and rs2486001 G/A in the SLC6A9 was performed by PCR-RFLP method as described previously [44], using the following published primers: SLC1A2 forward 5'-GAGCGGCGGGGCCTCTTTTC-3' and reverse 5'-TGCAGCCGCTGCCACCTGTG-3' [45], SLC6A9 forward 5'-TTCTATTCCCTGGGGTTCAGCA-3' and reverse 5'-AGCCTGGGCTGAGGCACACCAC-3' [43]. Ampli ed products were digested by two restriction enzymes (BcnI -rs4354668 and AvaII -rs2486001) (Thermo Fisher Scienti c), according to the protocol, and digested products were separated by electrophoresis in 2% agarose gels stained with ethidium bromide.…”
Section: Patient and Control Groups Pro Lementioning
confidence: 99%
“…However, in consideration of the etiology and pathophysiology of schizophrenia, no evidence has supported a proposal that GlyT1 is overexpressed in the brains of schizophrenic patients. In contrast, a series of negative findings of association studies have revealed that neither glycine transmission nor GlyT1 is implicated in the pathogenesis of schizophrenia (228)(229)(230). As described previously, although concentrations of glycine are 10-fold higher than D-serine, D-serine is considered the dominant endogenous coagonist of NMDARs and a modulator of NMDAR-related neurotoxicity (20,21).…”
Section: Non-sarcosine-based Glyt1 Inhibitorsmentioning
confidence: 92%